The Role of Reflective Journaling in Creative Writing Learning - Ramadhanti, Dina (South Sulawesi Education Development, 2024)
This research aims to describe the role of reflective journals in learning creative writing. By using a qualitative approach, information was obtained about student responses about the use of reflective journals in creative writing learning. Sixteen students were randomly selected to share their experiences using reflective journals. The research results show that students can creatively produce creative writing as a form of freedom of imagination and thinking creatively. In creative writing, the process starting from finding ideas, collecting written material, and evaluating needs to be the main consideration rather than the final product because good products are produced through a complex writing process. Reflective journals in this case help students monitor and control their freedom of thought.